PERAN LEMBAGA KEUANGAN PENYEDIA DANA MIKRO DALAM MENYEDIAKAN KESEMPATAN KERJA - Aryan Torrido (Jurnal Sosiologi Reflektif, 2014)
Micro fiance is an important tool for achieving development by the Government of Indonesia in three things directly: to create jobs, increase incomes, and reduce poverty. Access to sustainable fiancial services is a prerequisite for micro entrepreneurs to improve their business and reduce the vulnerability of poor families in the life ( to calamity and economic problems), as well as to increase their income. Micro fiance is an important tool in the country’s development strategy aimed at supporting the achievement of the Millennium Development Goals. The national policy for micro fiance is needed to overcome the limitations of micro fiance through the creation of an enabling environment for micro fiance institutions that already exist today to expand their services and to support the establishment of micro fiance institutions to fil the gap in demand and supply of micro fiance services especially in rural areas .